Bis(tetraphenylphosphonium) tetrachloridocobaltate(II) - Zeghouan Ouahida; Nasreddine Hadjadj; Fatiha Guenifa; Lamia Bendjeddou; Hocine Merazig (Acta Crystallographica Section E, 2014)
The title compound, (C24H20P)2[CoCl4], was prepared under hydrothermal conditions. In the crystal, the tetraphenylphosphonium cations are linked by pairs of weak C—H...π interactions into supramolecular dimers; the CoII cations lie on twofold rotation axes and the tetrahedral [CoCl4]2− anions are linked with the tetraphenylphosphonium cations via weak C—H...Cl hydrogen bonds.